Optimalisasi Peran Bhabinkamtibmas dalam Melakukan Pembinaan Masyarakat di Wilayah Hukum Polres Natuna - Hamdani Sitohang, Rifi; Perwita Sari, Rina (Bahtera Inovasi, 2026)
The role of Bhabinkamtibmas is the spearhead of the preemptive and preventive functions of the Indonesian National Police at the village and sub-district levels. However, suboptimal implementation of their duties is influenced by factors such as limited personnel, vast areas of responsibility, low support for facilities and infrastructure, and suboptimal coordination with local government officials and community leaders.This study aims to analyze efforts to optimize the role of Bhabinkamtibmas in carrying out community development in the Natuna Police jurisdiction. The objective is to create a safe, orderly, and conducive situation of security and public order as a tangible form of the Indonesian National Police's presence in the community.This study uses a Mixed Methods approach integrated with questionnaires and interviews involving Bhabinkamtibmas personnel across all Polsek ranks. Quantitative data was obtained through questionnaires using descriptive statistics and EFAS-IFAS mapping. Qualitative data from interviews, observations, and FGDs were combined for interpretation and analyzed using the SFAS technique.The conclusions of this study cover the state of human resource readiness, budget availability, the actual state of infrastructure, and the methods used. These findings lead to suggestions and practical recommendations to management.